Organizing for endangered and threatened species habitat in the Platte River Basin - Freeman, David M., author; Epperson, Annie, author; Lepper, Troy, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2003)
This study is an attempt to capture the essential shape of multiple sets of negotiations that have been on-going for more that a dozen years in the Platte River basin.
An Earlier Version Of This Report Was Presented To The Colloquium On Comparative Study Of Ecosystem Restoration Projects, Center for Ecosystem Science and Policy University of Miami School of Law, Coral Gables, Florida January 22-24, 2003.
September 2003.
Keywords: Endangered species -- Colorado; Endangered species -- Nebraska; Water -- Research -- Colorado; Habitat conservation -- Colorado; Habitat conservation -- Nebraska; Integrated water development -- Nebraska; Integrated water development -- Colorado